A Review- Mechanism Of Cough - Harsoliya, M.S (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTToday cough is the major persisting problem in the world. The current mortality statistics reveal the weighted average is 0.3 deaths per 1 million. The decompensatory events of coughing and choking in MND are multifactorial in origin. Various combinations of upper and lower motor neuron dysfunction result in respiratory muscle weakness, dysphasia and laryngeal dysfunction resulting in a range of different factors which may promote the need to cough but impair efficacy of coughing: the relative contributions and clinical importance of volitional and reflex (including emotional) activation to the swallowing, laryngeal and respiratory impairments is often unclear in MND patients. The cough reflex has both sensory (afferent) and motor (efferent) components. In auricular branch of the vagus nerve supplying the ear may also elicit a cough.